Modern VLSI design : - Wolf, Wayne Hendrix (PTR Prentice Hall, 1994)
This comprehensive, detailed view of up-to-date VLSI design techniques for custom digital integrated circuit design shows readers how to design a variety of digital chips -- ranging from CPUs to interface logic -- starting only with bare silicon. It covers all phases of the IC design process, and provides insight into how modern computer-aided (CAD) methods should be used in the process. Readers will understand the complete IC design process -- from defining what the chip does to designing a chip's layout and preparing the chip for manufacturing test.